The dogme approach to improve the four english skills in 3rd bgu level students at republica del ecuador educational unit - López Lojan , Edison Fernando (SATHIRI, 2023)
The purpose of this study is to propose the use of Dogme method to improve the current English material established by the Ministry of Education in order to enhance the academic performance. Highschool students need to feel more engaged and motivated with their learning process, thus they need more interesting material according to their needs. To achieve this goal, the current didactic material needs to be modified with an innovating content that includes comprehensible input depicted with association. For example teachers can include poems in a zero conditional class to make the content more appealing to the students. The purpose to employ this method is to excel the four English skills such as speaking, writing, reading, and listening in students of 3rd BGU level of Republica del Ecuador Educational Unit from Otavalo City. A descriptive investigation was applied using the deductive method with a sample of 45 students, a survey that contained a likert scale was performed on the students. The validation was determined by the technical judgment of three experts and the reliability of 0.749 showed a high internal consistency through the SPSS Statistics Visor. The results indicated the students´ necessity of understandable input in the English material as well as the urgency to improve their four English skills.